Being your best collection (6 books) (HBR emotional intelligence series., 2023)
Manage your energy--and your mood. How to be human at work. HBR's Emotional Intelligence Series features smart, essential reading on the human side of professional life from the pages of Harvard Business Review. Each book in the series offers proven research showing how our emotions impact our work lives, practical advice for managing difficult people and situations, and inspiring essays on what it means to tend to our emotional well-being at work. Uplifting and practical, these books explore the self-awareness and well-being skills that are critical to ambitious professionals who want to sustain their energy and productivity and bring the best version of themselves to work every day--even during difficult times. This specially priced, six-volume set includes: Energy + Motivation Resilience Self-Awareness Purpose Meaning + Passion Happiness Confidence.